Phenotypic and genetic diversities are not correlated in strains of the cyanobacterium Microcystis aeruginosa isolated in SW Spain. Las diversidades fenotípica y genética de cepas de la cianobacteria Microcystis aeruginosa aisladas en el SW de España no están correlacionadas - López-Rodas, Victoria; Costas, Eduardo; Flores-Moya, Antonio (Acta Botanica Malacitana, 2013)
English. The cyanobacterium Microcystis aeruginosa (Kützing) Kützing is notorious for forming extensive and toxic blooms but the genetic structure of natural populations, and in particular during blooms, remains to be explored. In order to add more knowledge about the genetic structure of M. aeruginosa, we compared phenotypic and genetic variabilities in seventeen strains of M. aeruginosa isolated from three adjacent water bodies in SW Spain (the consecutive reservoirs La Minilla and El Gergal, and small pools in Doñana National Park). For this purpose, a phenetic tree, based on six phenotypic traits (including morphology of cells, photosynthetic and respiratory performance, and toxin production) was compared with a phylogenetic tree built by using the 16S-23S rDNA Internal Transcribed Spacer sequence. Whereas the strains isolated from La Minilla showed a relatively homogeneous phenotype, the phenotypic traits of the remaining strains did not discriminate between the other two water bodies. On the other hand, only a strain isolated in Doñana National Park showed a slightly different ITS sequence, but the sequences from the remaining strains were similar. Possible explanations for this discrepancy between phenotypic and genetic diversities are discussed. Español. La cianobacteria Microcystis aeruginosa (Kützing) Kützing puede dar lugar a extensas floraciones tóxicas pero la estructura genética de las poblaciones naturales, y en particular durante las floraciones, ha sido escasamente estudiada. Con el objeto de profundizar en la estructura genética de M. aeruginosa, se han comparado las variabilidades fenotípica y genética de diecisiete cepas aisladas de tres cuerpos de agua adyacentes en el SW de España (los embalses consecutivos de La Minilla y El Gergal, y charcas en el Parque Nacional de Doñana). Para este fin, un árbol de similitud fenética basado en seis caracteres fenotípicos (que incluyen la morfología de las células, el rendimiento fotosintético y respiratorio y la producción de toxina) se comparó con un árbol filogenético construido mediante el uso de la secuencia de ITS 16S - 23S del ADNr. Las cepas aisladas en La Minilla mostraron un fenotipo relativamente homogéneo pero no se detectó un patrón de fenotipos que discriminase los otros dos cuerpos de agua. Por otro lado, sólo una cepa aislada en el Parque Nacional de Doñana mostró una secuencia ITS diferente, pero las secuencias de las cepas restantes fueron idénticas. Se discuten las posibles explicaciones para esta discrepancia entre la diversidad fenotípica y genética en M. aeruginosa.